The association between surgery for carpal and cubital tunnel syndrome: analysis of incidence and risk factors within a geographical area. (March 2021) - Johnson, Nick A.; Darwin, Oliver; Chasiouras, Dimitrious; Selby, Anna; Bainbridge, Chris
The relationship between surgery for cubital tunnel and carpal tunnel syndrome was examined in this retrospective study. Between 1997 and 2018, data from consecutive patients who underwent carpal tunnel release (8352 patients), cubital tunnel release (1681 patients) or both procedures (692 patients) were analysed. The relative risk of undergoing cubital tunnel release in the population who had carpal tunnel release compared with those with no carpal tunnel release was 15.3 (male 20.3; female 12.5). The relative risk of undergoing carpal tunnel release in the population who had cubital tunnel release compared with those who did not undergo carpal tunnel release was 11.5 (male 16.5; female 9.1). Our study showed that men and women who undergo carpal tunnel release are over 20 times and 10 times more likely to have cubital tunnel release than those who did not undergo carpal tunnel release, respectively. These findings suggest that the two conditions may share a similar aetiology. Level of evidence: IV